2015
DOI: 10.17221/7924-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Expression of innate immunity genes in kuruma shrimp Marsupenaeus japonicus after in vivo stimulation with garlic extract (allicin)

Abstract: ABSTRACT:In recent times, attention has focused on immunostimulants and plant products which could have beneficial effects in disease control. At present, the application of immunostimulants has been considered a more effective approach to health management in aquaculture through the enhancement of immune capability and disease resistance in shrimp. Garlic possesses bactericidal property against bacteria and can inhibit the growth of protozoa as well as gregarine infection in cultured shrimp. However, its effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…Garlic treated group showed significant upregulation in TNFα pre/post bacterial infection [58]. Sung et al [57] found that although garlic has increased LPS-induced TNF-α.…”
Section: Discussionmentioning
confidence: 96%
“…Garlic treated group showed significant upregulation in TNFα pre/post bacterial infection [58]. Sung et al [57] found that although garlic has increased LPS-induced TNF-α.…”
Section: Discussionmentioning
confidence: 96%
“…xidant enzyme activities of shrimp against V. alginolyti cus and WSSV infection (Wu et al 2015). The purified garlic compounds allicin and ajoene demonstrated immune stimulant capacity against fish pathogenic protozoa Spironucleus vortens and Ichthyophthirius multifiliis, and the bacteria A. hydrophila (Nya et al 2010;Tanekhy and Fall 2016). Recently, Foysal et al (2019) reported that dietary administration of garlic could modulate gut microbiota, increase recovery from streptococcus infection and upregulate the expression of immune genes in the intestinal tissue of tilapia.…”
Section: Discussionmentioning
confidence: 99%
“…As “prevention is better than treatment urged scientists to accept alternative management strategies such as using plant products in aquaculture, which is one of the promising alternatives to antibiotics, whereas, they stimulate the fish immune system, prevent stress and act as antimicrobial agents due to their active chemical ingredients (Assefa & Abunna, 2018). At present, many scientific literature has considered the potential use and adoption of several synthetic and/or organic plant derivatives for the treatment of aquaculture diseases, including synthetic polyphenol compound (Tinh et al, 2021), Mentha piperita peppermint (Talpur, 2014), Origanum vulgare L. (Abdel‐Latif et al, 2020; Mabrok & Wahdan, 2018) and garlic Allium sativum (Tanekhy & Fall, 2015). Oregano essential oil (OEO) is believed to have remarkable antibacterial activity, which is mainly attributed to its phenolic components such as carvacrol and thymol.…”
Section: Introductionmentioning
confidence: 99%